TWO-WAY COMMUNICATION AND DIGITAL TALENT EMPOWERMENT: ANALYSIS OF TELKOMSEL'S CSR PROGRAM AT RUMAH BUMN YOGYAKARTA - Dyas Dwi Azhar Rumeksa; Lukman Hakim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study analyzes PT Telkomsel's CSR program in developing the digital competency of the younger generation at Rumah BUMN Yogyakarta from a corporate communication perspective. Using a qualitative case study involving 10 informants (4 companies, 6 participants), data was collected through semi-structured interviews, observations, and document analysis using the Braun & Clarke thematic method. The findings indicate that Telkomsel's CSR program functions as a symmetrical two-way communication that not only transfers technical skills in digital literacy and entrepreneurship but also facilitates the empowerment process by increasing participants' self-confidence, communication skills, and entrepreneurial mindset. The communication dynamics between facilitators and participants demonstrate a dialogic, participatory approach, where participants are empowered through active participation and the construction of shared meaning. From the company's perspective, this program contributes to the construction of a corporate identity as an institution concerned with sustainable social development, not merely philanthropy or image building. The study concludes that CSR has the potential to be a transformative corporate communication instrument if designed with the principle of sustainable empowerment. This is an open access article under the CC–BY-SA license.